People with disabilities are ready to compete in the Business and Work World Industry (IDUKA) through Vocational Education - Aini, Sylvi Noor; Juhanaini, Juhanaini (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
This study aims to describe the process of developing vocational education for children with hearing barriers. The approach is carried out using a descriptive qualitative approach through research design that is carried out in 3 stages, namely the description stage, the reduction stage and the selection stage. The results of the study describe in full the process of vocational education for children with hearing barriers carried out at SLB bandung city. Data analysis is performed using data triangulation through various instruments. Vocational education at SLB became a provision to face the Business Industry and the World of Work (IDUKA), so SLB developed various programs to equip vocational skills in the form of soft skills and hard skills. Vocational education is an independence program that is being developed in the world of special education. Efforts carried out in vocational education can develop the ability of students to become capable human beings in the world of work through strengthening hard skills and soft skills in certain fields. Upaya link and match conducted in vocational education has an impact on preparing students to face the post-school world by aligning the school curriculum based on the competence and needs of the business industry and the world of work.